What is social resilience? Lessons learned and ways forward - Keck, Markus; Sakdapolrak, Patrick (ERDKUNDE, 2013)
Over the last decade, a growing body of literature has emerged which is concerned with the question of what form a promising concept of social resilience might take. In this article we argue that social resilience has the potential to be crafted into a coherent analytic framework that can build on scientific knowledge from the established concept of social vulnerability, and offer a fresh perspective on today’s challenges of global change. Based on a critical review of recently published literature on the issue, we propose to define social resilience as being comprised of three dimensions: 1. Coping capacities –the ability of social actors to cope with and overcome all kinds of adversities; 2. Adaptive capacities – their ability to learn from past experiences and adjust themselves to future challenges in their everyday lives; 3. Transformative capacities – their ability to craft sets of institutions that foster individual welfare and sustainable societal robustness towards future crises. Viewed in this way, the search for ways to build social resilience – especially in the livelihoods of the poor and marginalized – is revealed to be not only a technical, but also a political issue.